Pendampingan pembuatan abon jantung pisang pada kelompok ibu PKK di Desa Semperiuk A - Wahyu Wahyu; Amira Amira; Anggraini Anggraini; Ariska Ariska; Ayu Febby Puspita; Mia Talia; Novia Pipit Kurniawati; Rendi Agustian; Kiki Kristiandi (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2022)
Semperiuk A Village is one of the villages located in South Jawai District, Sambas Regency with a population density of 475.17/Km. The results of the village are agricultural commodities in the form of bananas, rice, deep coconuts, vegetables and fruits. Based on the potential of the region that bananas are the main commodity. However, the community in Semperiuk A Village has no product development that can be developed optimally. The purpose of this research is to increase the village's ability to make processed products, besides that this assistance is a product that is favored by the local village and becomes a product that can improve the economy in Semperiuk A Village, South Jawai District. The stages in this activity are divided into two, namely: 1. The preparation stage which includes the initial process of asking for permission to provide assistance in Semperiuk A Village. 2. The implementation stages of the activities carried out by the accompanying participants and respondents totaling 10 PKK women. The result of this activity is that this superior product of banana heart shredded has the potential to be consumed as an effort to diversify food. The PKK women will also plan for the banana heart shredded product to be the flagship product of Semperiuk A Village. The results of this mentoring activity can be used as a benchmark for local communities to take advantage of the potential of the land in their respective areas.